The Prophetic Disappearance of Thomas Merton - Dumont, Charles (Cistercian studies quarterly, 2002)
Focuses on the life of Thomas Merton. Link between Merton's spiritual reflections and his experiences; Revelation of Merton's imagination in seven volumes of his Journals; Description of vitality of his interior life by Merton; Search for the spiritual life in literature and poetry by Merton; Influence of writer James Joyce on Merton.